Cytological and cytochemical studies on the pulmonary alveolar macrophages of the rat “Rattus rattus norvegicus albinus” - Salman, Mohammad O.; Abd, Ali H.; Al-Ani, Imad Matloub Dally; Al-Salihi, Anam R. (Department of Anatomy, National University of Singapore, 2013)
The objective of the present study was to ﬁ nd the normal values of the cytology and cytochemistry of the Pulmonary Alveolar Macrophages (PAMs) and through the identiﬁ cation of universal normal values. Bronchoalveolar lavage (BAL) ﬂ uid was performed by tracheal cannulation to seventy healthy adult male rats. The percentages of differential BAL cells count were 85-90% PAMs, 5-6% lymphocytes, 3-4% granulocytes and 3-4% epithelial cells. The diameter of PAMs was ranging between (14-35μ). The mean of PAMs area was 57μ2±1.03. The mean of nucleus area was 17.6μ2±1.3. The ratio of nucleus areas to cytoplasm area was1:2. The Final Reaction Product of the ANAE was homogenous brown reddish color. It was homogenous in distribution although the distribution was regular within the area of cytoplasm and nucleus of PAMs while other BAL cells showed negative reaction. 95% of total PAMs were positive in reaction. The mean of optical density of ﬁ nal reaction product of esteratic activity in PAMs was 1.782±0.004.